ANALISIS PERAN PAJAK DAN SUBSIDI DALAM MENDUKUNG PEMBANGUNAN EKONOMI BERKELANJUTAN DI INDONESIA - Dwi Sintia Rahmawanti; Imahda Khoiri Furqon (Restitusi : Jurnal Riset Perpajakan, 2025)
This study aims to explore the extent to which taxes and subsidies play a role in supporting sustainable economic growth in Indonesia using a literature review method. The study was conducted by collecting and studying various secondary sources such as journals, books, and policy reports that describe the role of taxes as a source of state revenue, a tool for income redistribution, and a means of environmental regulation. Subsidies are studied as a fiscal tool that can provide protection to low-income communities and also encourage the development of environmentally friendly energy and sustainable technology. The findings of the study indicate that an effective combination of tax and subsidy policies is crucial to achieving sustainable development goals, especially in terms of poverty alleviation, improving social welfare, and protecting the environment. However, the successful implementation of this policy requires transparency, fairness, and optimal management in order to encourage inclusive and sustainable economic growth. This study provides significant contributions to policy makers in designing fiscal strategies that support sustainable national development.